2021
DOI: 10.1073/pnas.2108429118
|View full text |Cite
|
Sign up to set email alerts
|

IPM reduces insecticide applications by 95% while maintaining or enhancing crop yields through wild pollinator conservation

Abstract: Pest management practices in modern industrial agriculture have increasingly relied on insurance-based insecticides such as seed treatments that are poorly correlated with pest density or crop damage. This approach, combined with high invertebrate toxicity for newer products like neonicotinoids, makes it challenging to conserve beneficial insects and the services that they provide. We used a 4-y experiment using commercial-scale fields replicated across multiple sites in the midwestern United States to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 99 publications
3
39
0
Order By: Relevance
“…Could such an approach be used in other cropping systems? Certainly, each has its own challenges and attributes, but this work ( 7 ) suggests that the types of effects observed by Stuligross and Williams could be reduced with expanded IPM practices in areas where better bee stewardship is needed.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Could such an approach be used in other cropping systems? Certainly, each has its own challenges and attributes, but this work ( 7 ) suggests that the types of effects observed by Stuligross and Williams could be reduced with expanded IPM practices in areas where better bee stewardship is needed.…”
mentioning
confidence: 94%
“…For example, a recent study showed that using IPM in both a wind-pollinated field crop (maize) and a pollinator-dependent specialty crop (watermelon) resulted in no maize yield losses and improvements in watermelon yield. Further, within just a single year of using IPM, wild bee visitation of watermelon increased ( 7 ). Thus, an IPM approach could result in reduced insecticide use and improved yields and result in a rapid response by pollinators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IPM methods aimed at pest control might also benefit pollinating insects—key contributors to fruit growing—and improve yield and quality [ 5 , 6 , 7 ]. Indeed, IPM practices can increase crop yields through the preservation of pollinating insects [ 8 ]. Recently, Egan et al [ 9 ] proposed the introduction of a systematic framework for integrated pest and pollinator management (IPPM).…”
Section: Introductionmentioning
confidence: 99%
“…in the European Union all neonicotinoids except acetamiprid) after they have been proven to harm non-target insects (like bees) in addition to the pest species targetted. In fact, the transition to alternative agricultural practices is possible without yield losses (EPRS 2019) whilst pest damage can be reduced and farm profitability maintained after lowering, but not completely abandoning, pesticide use (Lechenet et al 2017; Pecenka et al 2021). Despite the increasing number of organic farms (European Commission n.d. a; Willer and Lernoud 2018) in the European Union, the process leading to biodiversity-friendly farming can take years because the current conventional plant protection strategies employed on non-organic farms still require synthetic pesticide input.…”
Section: Introductionmentioning
confidence: 99%